Precise bulk density measurement of planktonic foraminiferal test by X-ray microcomputed tomography - Kimoto, Katsunori; Horiuchi, Rika; Sasaki, Osamu; Iwashita, Tomohiro (Frontiers in Earth Science, 2023)
X-ray Microcomputed Tomography (µCT) is rapidly becoming an important analytical technique for examining the precise morphometry of small objects. The most notable feature of this technique is that it enables nondestructive, highly accurate morphometric measurements at micrometer-order resolution. In the Earth sciences, this makes µCT extremely useful for clarifying how genetic associations and the surrounding environment affect the morphology of micro-sized organisms. However, the actual analytical methods and the points that must be considered to produce reliable data have rarely been discussed in detail. Here, to address this lack of discussion, we describe in detail our methodology for precise µCT-based morphometry by using a test of the planktic foraminifer and marine calcifier Globorotalia inflata. In addition to demonstrating the long-term stability of our µCT setup and analytical approach, we also propose a new methodology for test bulk density calibration using artificial carbonate phantoms. We expect that µCT together with our artificial phantom-based methodology will be useful for calculating accurate test bulk densities of micro-sized marine calcifiers.